Wide Range Achievement Test in Autism Spectrum Disorder: Test-Retest Stability. Issue 3 (June 2015) - Jantz, Paul B.; Froehlich, Alyson L.; Cariello, Annahir N.; Anderson, Jeffrey; Alexander, Andrew L.; Bigler, Erin D.; Prigge, Molly B. D.; Travers, Brittany G.; Zielinski, Brandon A.; Lange, Nicholas; Lainhart, Janet E.
The principal goal of this descriptive study was to establish the test-retest stability of the Reading, Spelling, and Arithmetic subtest scores of the Wide Range Achievement Test (WRAT-3) across two administrations in individuals with autism spectrum disorder. Participants ( N = 31) were males ages 6–22 years ( M = 15.2, SD = 4.0) who were part of a larger ongoing longitudinal study of brain development in children and adults with autism spectrum disorder ( N = 185). Test-retest stability for all three subtests remained consistent across administration periods ( M = 31.8mo., SD = 4.1). Age at time of administration, time between administrations, and test form did not significantly influence test-retest stability. Results indicated that for research involving individuals with autism spectrum disorder with a full scale intelligence quotient above 75, the WRAT-3 Spelling and Arithmetic subtests have acceptable test-retest stability over time and the Reading subtest has moderate test-retest stability over time.